Multicultural Activities to Promote Cultural Tourism in Ko Kret, Nonthaburi Province - Phanmool, Jiranee; Phopunprom, Praphan (Area Based Development Research Journal, 2020)
Ko Kret community, Nonthaburi province is a multicultural society that Thai Buddhists, Thai Mon and Thai Muslims with a history of coexistence. The objectives of this research are therefore to select and organize cultural activities that integrate multi-cultural identities of Thai Buddhists, Thai Mon and Thai Muslims in Ko Kret through the participatory action research process. The research implementation was as follows: 1) Searching for common identities of multiculturalism; 2) Selecting cultural activities that reflect common identities, and 3) Creating guidelines for organizing cultural activities that reflect common identities. The guidelines for organizing cultural activities can be classified into 7 steps as follows: 1) Setting community goals; 2) Appointing working groups; 3) Planning; 4) Building networks; 5) Spreading the message and publicizing information; 6) Organizing activities; and 7) Monitoring and evaluation. The research shows that the cultural identities of Ko Kret is a result of communal appreciation and mutual acceptance presented through the “living together in peace” principle. Such aspect is observable through the community’s appreciation of their own history, fair shares in resources, and respect towards rules for coexistence. Additionally, the community’s presentation of their common identities through cultural performances that combine and integrate the features of performing arts among Thai Buddhists (Thai Dance), Thai Mon (Mon Dance) and Thai Muslims (Li-ke-hulu) during the Ko Kret Songkran festival contributes enormously to the communal pride. In summary, Ko Kret community appreciates the value of their common identities, takes great pride, and acknowledges the shared cultural space, while providing multi-cultural activities under the community mechanism collaboratively run by appointed committee and Ko Kret Subdistrict Administrative Organization, which promotes new trends in cultural tourism of Ko Kret.